Stylistic Analysis on the story of the Qur'an: Study of the Story of the Queen of Saba in An-Naml verses 20-44 - Nurul Imam, Jahira Salsabila; Soleh, Komarudin (Journal of Ulumul Qur'an and Tafsir Studies, 2023)
This study aims to examine the story of Ratu Saba in terms of plot, setting, characters, even the narrative style of the story of Ratu Saba contained in the Al-Qur'an An-Naml from verses 20 to 44. literary criticism through heuristic and retroactive reading so that the implicit meaning behind the story of Ratu Saba can be found, especially regarding women's leadership in the Qur'an. The study was studied using a qualitative content analysis research method with a stylistic approach and literary criticism as part of Stylistics. As for data collection, using library research. The writer traces and collects related verses, then analyzes the form of language contained in the verse. The problems that arise in this research are born from the problematic portrait of women's political leadership which is still considered taboo by some people, but in fact access to take part politically for women is wide open. The results of this study indicate that the results of a review of the elements of balaghah science in this story contain elements of bayan, badi and ma'ani. In addition, after carrying out literary criticism through semantic analysis, it can be concluded that the story of the Queen of Saba contained in Surat An-Naml verses 20-44 contains wisdom that there is equality (egality) between men and women in terms of leadership and faith in Allah SWT. . In addition, this story has quite high literary value, so that its form and content can be analyzed based on the rules that are usually owned by a literary work, moreover this story is contained in Holy Qur’an.